Predominance of Trichophyton tonsurans causing tinea capitis: A 12-year retrospective study in the north of Iran - Mohammad T. Hedayati; Firoozeh Kermani; Javad Javidnia; Mahmood Moosazadeh; Mohsen Nosratabadi; Maryam Salimi; sabrieh asadi; Elham Mosayebi; Zohreh Hajheydari; Masoud Golpour; Ghasem Rahmatpour Rokni; Armaghan Kazemi Nejad; et al. (Mazandaran University of Medical Sciences, 2023)
Background and purpose: Among different clinical entities of dermatophytosis, tinea capitis (TC) is considered a major public health challenge in the world, especially in regions with poor health and low income. Therefore, this study aimed to provide a retrospective analysis of the patients suspected of TC who were referred to the medical mycology laboratory of Mazandaran, a northern province of Iran.Materials and Methods: A retrospective analysis was performed on the patients suspected of TC who were referred to the medical mycology laboratory from July 2009 to April 2022. Hair roots and skin scrapings were collected from the participants. The laboratory diagnosis was confirmed by direct microscopic examination and culture. Finally, 921 out of 11095 (8.3%) patients were suspected of TC.Results: Based on the findings, TC was confirmed in 209 out of 921 patients (22.7%). In terms of gender, 209 TC patients (75.1%) were male. Moreover, the male to female ratio of TC patients was 1:3.0. Trichophyton tonsurans (146/174, 83.91%) was the most etiological agent,followed by T. mentagrophytes (13/174, 7.47%), T. violaceum (9/174, 5.17%), Microsporum canis (3/174, 1.71%), T. verrucosum (2/174, 1.15%) and T. rubrum (1/174, 0.57%). Besides, endothrix (77.0%) was the most prevalent type of hair invasion.Conclusion: The results revealed the predominance of T. tonsurans, as a causative agent of TC. Despite the prevalence of TC, the absence of appropriate consideration highlights that it is a neglected complication among children.